2019
DOI: 10.1177/0142331218818653
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven multi-inverter cooperative control for voltage tracking and current sharing in islanded AC microgrids

Abstract: A data-driven cooperative control scheme utilizing additional local and network sensor information is proposed for voltage tracking and current sharing under a cyber-physical system framework. An information-based inverter controller is developed as a replacement for the physical mechanism or model-based method because of uncertainties related to the inverter application scenario, system structure and specifications. To overcome the disadvantages of the reference voltage set-point strategy, an integrated casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In the last two decades, cooperative control of multi-agent systems (MASs) has gained considerable attention within the control community. These approaches found many applications in diverse areas such as microgrids (Meng and Hou, 2019), high-speed trains (Li et al, 2016), attitude synchronization in spacecraft (Zong et al, 2018), distributed generators (Fan et al, 2018), multi-missile systems (Jianguo et al, 2019), multiple quadrotor systems (Liao et al, 2019), multi-robotic networks (Wang et al, 2020), unmanned aerial vehicles (Liu YA et al, 2019; Wei et al, 2020), and path planning (Shen et al, 2019). One major the topic of interest in MASs is coordinated consensus problem aiming to steer the states of all agents in the network to some common value such as heading angle, velocity, and rendezvous position, merely relying on locally shared information (Rezaee and Abdollahi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, cooperative control of multi-agent systems (MASs) has gained considerable attention within the control community. These approaches found many applications in diverse areas such as microgrids (Meng and Hou, 2019), high-speed trains (Li et al, 2016), attitude synchronization in spacecraft (Zong et al, 2018), distributed generators (Fan et al, 2018), multi-missile systems (Jianguo et al, 2019), multiple quadrotor systems (Liao et al, 2019), multi-robotic networks (Wang et al, 2020), unmanned aerial vehicles (Liu YA et al, 2019; Wei et al, 2020), and path planning (Shen et al, 2019). One major the topic of interest in MASs is coordinated consensus problem aiming to steer the states of all agents in the network to some common value such as heading angle, velocity, and rendezvous position, merely relying on locally shared information (Rezaee and Abdollahi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The review of MFAC can be found in the literature [32][33][34]. At present, the model-free adaptive control method and its improved versions have been widely used in electromagnetic control [35], vibration control [36], water level control [37], electric energy control [38], traffic road network boundary control [39] and other fields. Meanwhile, recent research extended the application of model free adaptive control theory to trajectory-based aircraft operation [40].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to some smallscale islanded micro-grids, due to the small capacity and poor inertia of the system, one of the major challenges is to stabilize the frequency and amplitude of the alternating current (AC) bus voltage. 10,11 Generally, EVs are connected with the public power grid through V2G inverters. In the islanded power system with EVs as the main power source, V2G inverters are responsible for stabilizing the AC bus voltage.…”
Section: Introductionmentioning
confidence: 99%